2021
DOI: 10.31703/gsr.2021(vi-i).03
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Perceived Social Support in Perceived Stress and Quality of Life among Parents of Children with Special Needs

Abstract: The study was designed with the objective to examine the perceived social support (PSS) as a moderator between parental perceived stress (PPS) and quality of life (QOL) among parents having children with special needs. A sample of 300 parents was selected through purposive sampling from special education schools and health care centres of Lalamusa, Kharian, Gujrat and Gujranwala, Pakistan. Parental Perceived Stress Scale (PPSS), MultiDimensional Scale of Perceived Social Support (MDSPSS) and quality of life wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, our results concerning the psychological aspects of parents align with Karande et al's [16] findings, which indicate that mothers of children with Sp.L.D.s tend to exhibit higher levels of anxiety compared to other groups of mothers. Additionally, our findings concerning the necessity and success of the intervention program align with a study conducted by Kausar et al [37], which concluded that perceived social support plays a moderating role in the relationship between perceived stress and the QoL among parents of children with Sp.L.D.s. Moreover, our results further validate the importance of social support, as indicated in the study by Kuru and Piyal [38].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our results concerning the psychological aspects of parents align with Karande et al's [16] findings, which indicate that mothers of children with Sp.L.D.s tend to exhibit higher levels of anxiety compared to other groups of mothers. Additionally, our findings concerning the necessity and success of the intervention program align with a study conducted by Kausar et al [37], which concluded that perceived social support plays a moderating role in the relationship between perceived stress and the QoL among parents of children with Sp.L.D.s. Moreover, our results further validate the importance of social support, as indicated in the study by Kuru and Piyal [38].…”
Section: Discussionsupporting
confidence: 90%
“…tend to exhibit higher levels of anxiety compared to other groups of mothers. Additionally, our findings concerning the necessity and success of the intervention program align with a study conducted by Kausar et al (2021), which concluded that perceived social support plays a moderating role in the relationship between perceived stress and the QoL among parents of children with Sp.L.D. Moreover, our results further validate the importance of social support, as indicated in the study by Kuru & Piyal (2018).…”
Section: Discussionsupporting
confidence: 87%